Too Much of a Good Thing: Displays in Contacts and "Engagement Disloyalty" in Rainbows End by Vernor Vinge. Issue 3 (December 2019) - Kozioł, Sławomir
Abstract : Vernor Vinge's Rainbows End (2006) depicts a vision of the near future dominated by the use of powerful wearable computers equipped with displays integrated into contact lenses which not only provide non-stop visual access to the internet but also enable augmented reality. Drawing on the recent research indicating negative effects of the distractive potential of the present mobile communication technologies I focus on the capacity of smart contacts as they are represented in Vinge's novel to further encourage a type of multitasking that—because of its negative consequences—could be termed, using the term introduced by the sociologist Erving Goffman, "engagement disloyalty."